2016
DOI: 10.1038/srep38185
|View full text |Cite
|
Sign up to set email alerts
|

Test of quantum thermalization in the two-dimensional transverse-field Ising model

Abstract: We study the quantum relaxation of the two-dimensional transverse-field Ising model after global quenches with a real-time variational Monte Carlo method and address the question whether this non-integrable, two-dimensional system thermalizes or not. We consider both interaction quenches in the paramagnetic phase and field quenches in the ferromagnetic phase and compare the time-averaged probability distributions of non-conserved quantities like magnetization and correlation functions to the thermal distributi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 87 publications
1
31
0
Order By: Relevance
“…⊗ |s N of a many-body Hilbert space, where the s l label the local basis, the coefficients of the wave function |ψ are expressed as ψ( s) = s|ψ = e H ( s) (1) where H ( s) is an effective Hamilton function defining the classical network. Wave functions of this form were used in combination with Monte Carlo algorithms for variational ground state searches [14][15][16] and time evolution [17][18][19][20][21][22][23]. Recently, it was suggested that the wave function (1) can generally be encoded in an artificial neural network (ANN) trained to resemble the desired state [23].…”
Section: Introductionmentioning
confidence: 99%
“…⊗ |s N of a many-body Hilbert space, where the s l label the local basis, the coefficients of the wave function |ψ are expressed as ψ( s) = s|ψ = e H ( s) (1) where H ( s) is an effective Hamilton function defining the classical network. Wave functions of this form were used in combination with Monte Carlo algorithms for variational ground state searches [14][15][16] and time evolution [17][18][19][20][21][22][23]. Recently, it was suggested that the wave function (1) can generally be encoded in an artificial neural network (ANN) trained to resemble the desired state [23].…”
Section: Introductionmentioning
confidence: 99%
“…Our study of the 2D QDM combines a number of features that have proven to be of interest in other recent work on ETH [14][15][16][17][18]: First, it continues the progress of ETH studies from the familiar territory of 1D systems [19][20][21][22] into higher dimensions. Questions about ETH in systems in two or more dimensions, such as the transverse-field Ising model on the square lattice [14][15][16], are of great interest but challenging due to the rapid increase of the Hilbert-space dimension with system size.…”
Section: Introductionmentioning
confidence: 99%
“…Questions about ETH in systems in two or more dimensions, such as the transverse-field Ising model on the square lattice [14][15][16], are of great interest but challenging due to the rapid increase of the Hilbert-space dimension with system size. Second, the Hilbert space of the QDM is spanned by dimer configurations subject to strong local constraints.…”
Section: Introductionmentioning
confidence: 99%
“…We achieve many-body states with longer-range antiferromagnetic correlations by implementing a near-adiabatic quench of the longitudinal field and study the buildup of correlations as we vary the rate with which we change the field. Lattice quantum spin models serve as a paradigm for exploring a range of many-body phenomena, including quantum phase transitions [1,2], equilibration and thermalization [3,4], and quench dynamics [5][6][7][8][9][10]. While there exists a variety of well-developed theoretical techniques to study the equilibrium properties of quantum spin systems [11][12][13][14][15][16][17], the toolkit for simulating real-time dynamics of these systems is rather limited and can only capture the evolution accurately for short times, especially for systems in more than one dimension [11,[18][19][20].…”
mentioning
confidence: 99%